Rare copy number variants in the genome of Chinese female children and adolescents with Turner syndrome. Issue 1 (11th January 2019) - Li, Li; Li, Qingfeng; Wang, Qiong; Liu, Li; Li, Ru; Liu, Huishu; He, Yaojuan; Lash, Gendie E.
Abstract : Turner syndrome (TS) is a congenital disease caused by complete or partial loss of one X chromosome. Low bone mineral status is a major phenotypic characteristic of TS that can not be fully explained by X chromosome loss, suggesting other autosomal-linked mutations may also exist. Therefore, the present study aimed to detect potential genetic mutations in TS through examination of copy number variation (CNV). Seventeen patients with TS and 15 healthy volunteer girls were recruited. Array-based comparative genomic hybridization (a-CGH) was performed on whole blood genomic DNA (gDMA) from the 17 TS patients and 15 healthy volunteer girls to identify potential CNVs. The abnormal CNV of one identified gene ( CARD11 ) was verified by quantitative PCR. All cases diagnosed had TS based on genotype examination and physical characteristics, including short stature and premature ovarian failure. Three rare CNVs, located individually at 7p22.3, 7p22.2, and Xp22.33, where six genes ( TTYH3, AMZ1, GNA12, BC038729, CARD11, and SHOX (stature homeobox)) are located, were found in TS patients. Quantitative PCR confirmed the CNV of CARD11 in the genome of TS patients. Our results indicate that CARD11 gene is one of the mutated genes involved in TS disease. However, this CNV is rare and its contribution to TS phenotype requires further study.